Test of Drip Water Application on Saccharum officinarum Linn. and Dreg Litter on Physical and Chemical Fertility of Mollisol Soil and Plant Growth of Allium Schoenoprasum (L.) Chives. - Erwin Junaidi Lubis (Journal of Agribusiness and Natural Resources, 2025)
The content of Saccharun officinarum Linn. is a plant that contains water which is very sweet and good for human health and very good for the soil because the water contained in Saccharun officinarum Linn. is very good and can increase soil fertility and contains important nutrients, namely nutrients N, P, and K. Saccharun officinarum Linn. water droplets play an important role as a natural liquid organic fertilizer that can improve soil structure and the ability of plant roots and soil to absorb nutrients. Allium schoenoprasum (L.) Chives is one type of plant including leeks which is widely used as an additional seasoning for cooking, and is commonly referred to as Lokio or Lengkio or also hobo leeks. Growth in this hobo leek plant really requires a lot of nutrients or macro nutrients N, P, and K as a process of growth, as well as good and fertile soil media as a place of growth.